PERUMUSAN VISI YANG VISIONER DAN PERUMUSAN MISI PENDIDIKAN YANG IDEAL - Fiandi, Arif; Ilmi, Darul (Jurnal Manajemen Pendidikan, 2022)
In simple terms the word vision refers to an ideal, desire, wishful thinking, fantasy and ideal dream to be achieved in the future which is formulated in a simple, brief, solid and clear way but contains a broad, distant and meaningful meaning. Visionary leadership is a pattern of leading by determining a shared vision in accordance with the demands of change in society then giving instructions to people within the organization to work according to the vision that has been set together so that the results of the work realized will be in accordance with the vision. Educational mission is something that must be carried out as an elaboration of the vision that has been set within a certain period of time to be a reference for program preparation and to provide flexibility and space for the development of educational unit activities, based on input from all members of the education unit. The mission can be reviewed and reformulated periodically in accordance with developments and challenges in the community